Bureaucratic Reform and Service Innovation in a Village Government Institution - Agus B; Sabran Sabran; Aini Aini (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Bureaucratic reform is a strategic agenda for creating clean, accountable, responsive, and citizen-oriented governance. This study aims to analyze the implementation of bureaucratic reform and public service innovation in a village government institution, with particular attention to their role in improving service quality and community satisfaction. A qualitative descriptive approach was employed to examine two main aspects: the contribution of bureaucratic reform to service performance improvement and the forms of service innovation implemented, along with their effects on service accessibility, efficiency, and inclusiveness. The findings indicate that bureaucratic reform has been implemented relatively well, as reflected in simplified service procedures, strengthened accountability, and greater transparency in administrative processes. Several service innovations have also been introduced, including digital-based administrative services and outreach-based service delivery programs that bring public services closer to the community. These innovations have improved access to services, particularly for vulnerable groups and residents with limited mobility. In addition, community participation in decision-making has increased through communication forums linking village authorities and citizens. However, the implementation of bureaucratic reform continues to face challenges, especially limited human resource capacity and inadequate technological infrastructure. The study therefore recommends strengthening staff capacity, improving information technology facilities, and expanding community participation to support the sustainability of bureaucratic reform and the delivery of higher-quality public services.